Traditional Chinese medicine Yisui Tongjing relieved neural severity in experimental autoimmune neuritis rat model - Zhang E; Li M; Zhao J; Dong Y; Yang X; Huang J (Neuropsychiatric Disease and Treatment)
Erli Zhang,1 Mingquan Li,2 Jianjun Zhao,2 Yuxiang Dong,1 Xueqin Yang,1 Jingbo Huang1 1Department of Traditional Chinese Medicine, The First Bethune Hospital of Jilin University, 2Department of Encephalopathy, The First Affiliated Hospital of Changchun University of Traditional Chinese Medicine, Changchun, People’s Republic of China Objective: To study the effect of Yisui Tongjing (YSTJ) prescription on motor nerve conduction velocity (MNCV) and microstructure of the sciatic nerve in experimental autoimmune neuritis (EAN) rats, the Guillain–Barré syndrome classic animal models.Materials and methods: In this study, we established an EAN model in Lewis rats by immunization. We evaluated the potential clinical application of a traditional Chinese medicine YSTJ by intragastric administration and compared its effect with immunoglobulin. The sciatic MNCV was measured by electrophysiology experiment. Hematoxylin–eosin staining and transmission electron microscope analysis were used to determine the pathologically morphological changes before and after YSTJ application.Results: We found that application of YSTJ could significantly alleviate the clinical signs in EAN rats. The treatment also increased MNCV in the sciatic nerve compared to that in the untreated nerve. Demyelination in the sciatic nerve in EAN rats was significantly ameliorated, and newly generated myelinated nerve fibers were observed with treatment of high dose of YSTJ.Conclusion: This study showed that the traditional Chinese medicine YSTJ was likely to serve as a therapeutic medicine in autoimmune neuropathies, providing an effective and economic means to the treatment of Guillain–Barré syndrome. Keywords: Yisui Tongjing, experimental autoimmune neuritis, motor nerve conduction velocity, sciatic nerve, demyelination